Notes on the Bees of Southern Maine: Anthophoridae, Halictoididae, Macropidae and Panurgidae - J. H. Lovell; T. D. A. Cockerell (Psyche: A Journal of Entomology)
The Anthophoridae, which are represented by numerous species in the Middle States, become comparatively rare in northern New England. At Waldoboro in southern Maine there have been taken as the result of much diligent collecting only five species of Melissodes and one of Clisodon. With few exceptions, which will be noted under the respective species, they are visitors in this locality of the Compositae and fly during midsummer and early autumn. With the exception of Melissodes desponsa Sm., which is rather common, they might easily escape the attention of the general entomological collector.